2016
DOI: 10.1155/2016/8182096
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Extended-Spectrumβ-Lactamase- and AmpCβ-Lactamase-ProducingEscherichia coliwithin the Food Distribution System of Ho Chi Minh City, Vietnam

Abstract: To investigate the dissemination of ESBL/pAmpC-producing E. coli within the food distribution system of Ho Chi Minh City (HCMC), Vietnam, the prevalence of ESBL/pAmpC-producing E. coli strains in chicken meat, pork, beef, and fish/shrimp samples obtained from slaughterhouses, a wholesale market, and supermarkets was examined. Among the total of 330 collected food samples, ESBL/pAmpC-producing E. coli was detected in 150 samples (45.5%). The highest prevalence of these isolates was in chicken meat (76/82, 92.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 34 publications
(44 reference statements)
4
26
2
Order By: Relevance
“…The prevalence of E. coli in chicken samples 12% was nearly similar with that was reported by Momtaz et al (2012) and Zende et al (2013) who reported that the incidence of E.coli in chicken meat was 11% and 16.67 %, respectively. On the other hand, the present results were lower than those reported by Hyun-jung et al (2015) and Nguyen et al (2016) who reported E.coli presented in chicken meat with percentage 75.9% and 92.7%, respectively. These differences could be attributed to the hygienic measures proceeded in different localities under investigation and health condition of the meat handlers.…”
Section: Discussioncontrasting
confidence: 95%
“…The prevalence of E. coli in chicken samples 12% was nearly similar with that was reported by Momtaz et al (2012) and Zende et al (2013) who reported that the incidence of E.coli in chicken meat was 11% and 16.67 %, respectively. On the other hand, the present results were lower than those reported by Hyun-jung et al (2015) and Nguyen et al (2016) who reported E.coli presented in chicken meat with percentage 75.9% and 92.7%, respectively. These differences could be attributed to the hygienic measures proceeded in different localities under investigation and health condition of the meat handlers.…”
Section: Discussioncontrasting
confidence: 95%
“…A likely explanation to this high level of nonsusceptibility could be the extensive use of antimicrobial in chickens in Vietnam, often without veterinary prescription, as reported in many studies [1719]. Other studies have reported similar levels of AMR in E. coli from poultry in Vietnam [26, 27]. In contrast, the level of nonsusceptibility to 3GC was very low (3.9%) in indicator isolates, agreeing with the prevalence of 3.1% of resistance reported in 3GC in Vietnam [27].…”
Section: Discussionmentioning
confidence: 97%
“…The authors showed that all strains of the Enterobacteriaceae family showed to be AmpC enzyme carriers and showed resistance to at least 6 classes of antimicrobials, including beta-lactams. The presence of these multiresistant multi-resistant strains is a concern for public health and suggests that the use of antimicrobial agents in fish culture is to be strictly controlled 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteria are often associated with drug resistance and contamination of fish and shrimp 1 . Food contamination with multidrug-resistant bacteria, particularly extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae, is considered a potential source for the wide dissemination of ESBL-producing bacteria in communities 2 .…”
Section: Introductionmentioning
confidence: 99%